Design and Characterization of a Therapeutic Non-Phospholipid Liposomal Nanocarrier with Osteoinductive Characteristics to Promote Bone Formation - Cui, Zhong-Kai (ACS Nano, 2017)
Sterosomes are a recently developed type of non-phospholipid liposomes formed from single-chain amphiphiles and high content of sterols. Although sterosomes presented significantly increased stability compared to conventional phospholipid liposomes, current sterosome biomaterials are not truly bioactive and have no intrinsic therapeutic effects. The purpose of this study was to develop a sterosome formulation with osteoinductive properties by an effective selection of sterol, one of the sterosome components. Oxysterols are oxidized derivatives of cholesterol and are known to stimulate osteogenesis and bone formation. Thus, 20S-hydroxycholesterol (Oxy), one of the most potent oxysterols for bone regeneration was examined as a promising candidate molecule to form fluid lamellar phases with a single-chain amphiphile, namely stearylamine (SA). First, the optimal composition was identified by investigating the phase behavior of SA/Oxy mixtures. Next, the capacity of the optimized SA/Oxy sterosomes to promote osteogenic differentiation of bone marrow stromal cells was assessed in vitro in a hydrogel environment. Furthermore, we explored the effects of osteogenic oxysterol sterosomes in vivo with the mouse critical-sized calvarial defect model. Our results showed that SA/Oxy sterosomes induced osteogenic differentiation in vitro and enhanced calvarial healing without delivery of additional therapeutic agents, indicating their intrinsic bone forming potential. This study suggests a promising non-phospholipid liposomal platform with osteoinductive properties for delivery of small molecular drugs and/or other therapeutic genes for enhanced bone formation.